Multi-Volume Analysis of Nucleic Acids Using the EPOCH™ Spectrophotometer System - Brescia, P.; Banks, P.; Voloshin, А. (Наука та інновації, 2012)
Nucleic acids isolated from a variety of sample types provide the starting material for a broad range of downstream applications. Quantification of isolated nucleic acid is necessary prior to introduction into these applications. The Epoch Spectrophotometer System provides a mean of obtaining accurate measurement over a wide range of sample concentrations and volumes, including micro-volume quantification. Comparison to other micro-volume dedicated devices shows equivalent performance. Нуклеїнові кислоти, що виділяються з різноманітних типів зразків, є вихідним материалом для численних подальших досліджень. Для їх виконання необхідна кількісна оцінка ізольованих нуклеїнових кислот. Спектрофотометр Epoch забезпечує надійні вимірювання у широкому діапазоні концентрацій і об’ємів, у тому числі квантифікацію у мікрооб’ємі, та демонструє відмінні характеристики порівняно до інших пристроїв. Нуклеиновые кислоты, выделяемые из разнообразных типов образцов, являются исходным материалом для многочисленных дальнейших исследований. Для их выполнения необходима количественная оценка изолированных нуклеиновых кислот. Спектрофотометр Epoch обеспечивает надежные измерения в широком диапазоне концентраций и объемов, включая квантификацию в микрообъеме, и демонстрирует отличные характеристики в сравнении с другими устройствами.